# How to solve 1/2+2/m-6/2m=9m

Welcome to my article How to solve 1/2+2/m-6/2m=9m. This question is taken from the simplification lesson.
The solution of this question has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.
For complete information on how to solve this question How to solve 1/2+2/m-6/2m=9m, read and understand it carefully till the end.

Let us know how to solve this question How to solve 1/2+2/m-6/2m=9m.

First write the question on the page of the notebook.

## How to solve 1/2+2/m-6/2m=9m

We will solve this question by writing it as follows.

\displaystyle \frac{1}{2}+\frac{2}{m}-\frac{6}{{2m}}=9m

\displaystyle \frac{{1\times m+2}}{m}-\frac{6}{{2m}}=9m

\displaystyle \frac{{\left( {m+2} \right)\times 2}}{{m\times 2}}-\frac{6}{{2m}}=9m

\displaystyle \frac{{2m+4}}{{2m}}-\frac{6}{{2m}}=9m

\displaystyle \frac{{2m+4-6}}{{2m}}=9m

\displaystyle \frac{{2m-2}}{{2m}}=9m

\displaystyle 2m-2=18{{m}^{2}}

\displaystyle 2m-2-18{{m}^{2}}=0

\displaystyle -2\left( {-m+1+9{{m}^{2}}} \right)=0

\displaystyle \left( {-m+1+9{{m}^{2}}} \right)=0

\displaystyle 9{{m}^{2}}-m+1=0

we use the quardratic formula :

\displaystyle m=\frac{{-b\pm \sqrt{{{{b}^{2}}-4ac}}}}{{2a}}

a = 9

b = -1

c = 1

putting the value in this formula .

\displaystyle m=\frac{{-(-1)\pm \sqrt{{{{{(-1)}}^{2}}-4\times 9\times 1}}}}{{2\times 1}}

\displaystyle m=\frac{{1\pm \sqrt{{1-36}}}}{2}